Síndrome de Prune Belly com fístula vesicocutânea: relato de caso raro e revisão da literatura - Debora Leticia Silva Gouvêa Viana; Naara Rafaela Gonçalves; Álvaro Henrique Anghietti Nalon; Michel Correia Viana; Rúbia Cecília Barbone e Melo; Ítalo Guilherme Giarola de Freitas Mariano; Raquel Ida Ferreira; Thais Silva Maia; Paula Silva Maia (Residência Pediátrica, 2023)
Prune Belly syndrome (PBS) is a rare complex malformation that preferentially affects male newborns. It presents with a wide spectrum of alterations that include abdominal muscle deficiency, varying degrees of renal dysplasia and urinary tract obstruction, in addition to bilateral cryptorchidism. In general, it is associated with other developmental anomalies, mainly of cardiac, pulmonary and gastrointestinal origin. Despite numerous advances in the treatment of complex malformations, morbidity and mortality in PBS remains high, due to early renal failure and associated malformations. This is a case report of a male newborn, inserted in a complex social context, born by vaginal delivery, premature, with a gestational age of 36 weeks and 1 day. At the initial assessment in the delivery room, he presented: male external genitalia, bilateral cryptorchidism, flabby and hollowed abdomen, parchment skin suggestive of the absence of abdominal muscles, mild respiratory effort and bradycardia. He received positive pressure ventilation and was referred to the Neonatal Intensive Care Unit (UTIn) where a vesicocutaneous fistula and renal failure were found, despite the vesicostomy, progressing to death at 1 month and 1 day of chronological age. Complex congenital malformations, such as PBS, require individualized assessment so that better postnatal results are achieved. However, the limitation of therapeutic care must be carefully evaluated, considering the great morbidity that accompanies these patients. This article aims to describe a rare case of PBS, detailing the evolution of patients with this malformation.